APPLICATION OF LEARNING TECHNOLOGY IN THE NETWORK (SPEEDER) FOR OPTIMIZATION OF TEACHING AND LEARNING PROCESS AT SMK PALAPA - Adhie Thyo Priandika; Permata Permata; Rakhmad Dedi Gunawan; Temi Ardiansah; Mico Fahrizal; Anggun Maylani; Anissa Anggraini (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
The learning procedures carried out at this time during the pandemic have utilized learning media through whatsapp, google classroom and google form. The learning process starts from giving materials to students that are delivered or shared to whatsapp groups media and then students work on questions or materials given by each teacher. The online learning system at SMK Palapa as a support for learning is carried out using a website consisting of admin, teachers and students. The procedure for presenting materials is carried out in each online class made by the teacher in accordance with the designed syllabus, then students can see the materials and discussion forums conducted online. The online learning system at SMK Palapa as a learning support is carried out by accessing the online system, each student will get online class information to be able to enter the online classroom activities, students can see materials, see assignments and send answers and see the value of the results of the tasks done.